2023
DOI: 10.1001/jamanetworkopen.2023.40148
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Cancer Treatment During the First Year of the COVID-19 Pandemic in the US

Lauren M. Janczewski,
Joseph Cotler,
Ryan P. Merkow
et al.

Abstract: ImportanceThe COVID-19 pandemic created challenges to the evaluation and treatment of cancer, and abrupt resource diversion toward patients with COVID-19 put cancer treatment on hold for many patients. Previous reports have shown substantial declines in cancer screening and diagnoses in 2020; however, the extent to which the delivery of cancer care was altered remains unclear.ObjectiveTo assess alterations in cancer treatment in the US during the first year of the COVID-19 pandemic.Design, Setting, and Partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…This temporary period of early pandemic under-diagnosis was also noted by recent larger study of multiple high-risk gastrointestinal cancers. 15 There was no significant difference overall in time from symptom onset to the first clinical encounter. However, female patients detected an increase in time from symptom onset to referral to a specialty surgical oncology practice, postulated to occur due to delays in working up nonspecific symptoms for biliary tract-specific cancers.…”
Section: Discussionmentioning
confidence: 89%
“…This temporary period of early pandemic under-diagnosis was also noted by recent larger study of multiple high-risk gastrointestinal cancers. 15 There was no significant difference overall in time from symptom onset to the first clinical encounter. However, female patients detected an increase in time from symptom onset to referral to a specialty surgical oncology practice, postulated to occur due to delays in working up nonspecific symptoms for biliary tract-specific cancers.…”
Section: Discussionmentioning
confidence: 89%
“…These findings are contradictory to the hypotheses described in numerous prior studies, illustrating diagnostic and treatment delays that were projected to substantially affect survivorship . However, prior work using the NCDB to evaluate alterations in cancer treatment during the pandemic demonstrated a substantial decrease in time to treatment initiation which may contribute to the consistency in survival curves in the current study. Although this cohort of patients will be followed over time, it is unlikely that mortality rates at further time points will differ substantially, given the present results.…”
Section: Discussionmentioning
confidence: 99%
“… 13 Previous work analyzing the data collection infrastructure of the NCDB during the pandemic demonstrated that case abstraction remained intact, validating the use of this comprehensive, national database in future cohorts. 14 Although prior studies have evaluated national-level changes in cancer diagnosis 5 and treatment, 15 , 16 , 17 , 18 additional site-specific analyses are essential to understand what happened as a result of the pandemic and to anticipate changes in patient needs moving forward. We hypothesized that during the onset of the pandemic, there was a period of underdiagnosis as well as an increase in patients presenting with advanced-stage disease.…”
Section: Introductionmentioning
confidence: 99%